Adoption of Improved Wheat Varieties in Nawalparasi West District, Nepal - Acharya, Aayushma; Bhatta, Sushmita; Mishra, Binayak Prakash (Journal of Agriculture and Forestry University, 2026)
The adoption of improved wheat (Triticum aestivum L.) varieties is crucial for enhancing productivity and ensuring food security in Nepal. The study aimed to examine the adoption of improved wheat varieties in Nawalparasi West district, Nepal. It focused on adoption patterns, the factors influencing adoption, and the reasons for farmers’ decisions to adopt or not adopt these varieties. Additionally, the study explored farmers’ information sources, perceptions, and support needs. Primary data were collected in 2025 from 120 randomly selected farmers using a pretested semi-structured interview schedule. The results reveal that adoption of improved wheat varieties was positively influenced by male-headed households, commercial nature of production, and access to input markets. A negative association with adoption was observed for education and access to output markets. The varieties Vijay and Bhrikuti were adopted for longer periods and comparatively over larger farm areas. Farmers who did not adopt improved varieties reported unfamiliarity with benefits and high seed costs as the main reasons for nonadoption. Adopters highlighted high yield, superior grain quality, and disease/pest resistance as the reasons for adoption. Major challenges in the adoption of improved varieties were limited access to fertilizers and irrigation, and insufficient technical knowledge of recommended production practices. Fellow farmers and farmer groups or cooperatives were the major sources of information on improved varieties. Farmers expressed positive perceptions regarding yield, grain quality, and pest/disease resistance, and emphasized the need for support on resources and subsidies. Thus, strengthening access to input markets and fostering a shift toward commercial oriented production systems are crucial for accelerating the adoption of improved varieties.